EXPRESSIVE SPEECH ACTS TO REFLECT SOCIAL SUPPORT ABOUT MENTAL HEALTH IN @GEMMACORRELL’S INSTAGRAM COMMENTS - Adwidya Yoga; Ni Gusti Ayu Roselani (PT Akselerasi Karya Mandiri, 2024)
This research was initially prompted by the language used in Instagram to address mental issues in America. American society tends to express the psychological or mental states and experiences on social media, particularly Instagram. Hence, dealing with psychological expressions, this research deployed the analysis of expressive speech acts aimed at identifying the types of expressive speech acts and how they were delivered in communication -strategies. The data were taken from @gemmacorrell’s selected comment section. The analysis resulted in the finding of 7 out of 12 types of expressive speech acts utilization with the most usage order was compliment (39), lament (11), thank (7), congratulate (1), deplore (1), protest (1), and welcome (1). Further, most utterances denoted explicit, direct, and literal strategies without covering implied meanings. Regarding social dimensions, this research found that American society tended to share their problems with unknown virtual relatives, as it can be a signal that ‘real’ humanity is declining to be replaced by ‘virtual’ humanity. It is such an irony because in real life, people seem not to care about each other but in digital reality, they support each other. Hence, the researchers motivate scholars worldwide to initiate advanced studies on the phenomenon of language, social media, digital society, and mental health issues.